Congenital Nephroblastoma in a Buffalo Calf - Devi, Vemuri Rama; Veeraiah, Galan; Yedukondalu, Kolagani; Begum, Shaik K.; Annapurna, Pillutla; Sunitha, Penumaka; Devi, Matha A. (Brazilian Journal of Veterinary Pathology, 2011)
A nine years old, Graded Murrah she buffalo was brought to the veterinary hospital with clinical signs of labour and dystocia. A caesarian section was performed and a dead male calf was noticed in the uterus. At necropsy, the calf had distended abdomen with the presence of an enlarged mass. Histopathologically, the tissue sections from the mass revealed the presence of blastemal cells forming glomeruli like structures and tubules in some areas and mesenchymal tissue suggesting a congenital nephroblastoma that developed during fetal life resulting in maternal dystocia and death of the calf.